(untitled) (Colombia Medica, 1989)
The different assessment instruments or scales used in psychiatry measure symptoms such as depression, distress, or social maladjustment but do not allow a total assessment of the patient’s functioning. The Endicott Global Assessment Scale is an adequate and valid instrument to measure the overall severity of the patient at a given time or over a period from the onset of the severe psychiatric disorder to health. The evaluation of 32 clinical histories by two psychiatrists shows a high correlation coefficient (0.86) and ensures reliability in its use. It is a useful instrument for evaluating inpatients and outpatients in specialized hospitals or primary care centers. It also allows for predicting relapses and developing preventive actions.